Statistical analysis of the development of serfdom farms in the Vilnius and Dysna districts in the middle of the 19th century - Stasys Pamerneckis (Lietuvos Istorijos Studijos)
This article is written with the application of correlation-regression and factorial statistical models for researching corvee-peasant farms. In the richest peasant farms of the third group most intensive correlations connections were formed.